Quantification of Serum High Mobility Group Box 1 by Liquid Chromatography/High-Resolution Mass Spectrometry: Implications for Its Role in Immunity, Inflammation, and Cancer - Weng, Liwei; Guo, Lili; Vachani, Anil; Mesaros, Clementina; Blair, Ian A (Analytical chemistry (Washington), 2018)
High mobility group box 1 (HMGB1) is a non-histone chromosomal protein, which can be secreted through a variety of pathways and bind to pattern recognition receptors to release pro-inflammatory cytokines. Previous studies have suggested that HMGB1 is upregulated in numerous inflammatory diseases and that it could be a biomarker for such diseases. However, these studies used immunoassay-based methods to analyze serum HMGB1. Autoantibodies to HMGB1 in serum are found in healthy control subjects as well as in patients with different diseases. HMGB1 also binds to haptoglobin, a highly abundant plasma protein. This means that antibodies used in immunoassays must compete with binding of HMGB1 to endogenous serum HMGB1 autoantibodies and haptoglobin. To overcome these potential problems, we developed and validated a specific and sensitive assay based on stable isotope dilution and immunopurification to quantify HMGB1 in plasma and serum using two-dimensional nano-ultra-high-performance liquid chromatography parallel reaction monitoring/high-resolution mass spectrometry. Using this assay, we found that serum HMGB1 in 24 healthy control subjects (6.0 ± 2.1 ng/mL) was above the mean concentration reported for 18 different diseases (5.4 ± 2.8 ng/mL) where the analyses were conducted with immunoassay methodology. In light of our finding, the role of HMGB1 in these diseases will have to be re-evaluated. The concentration of HMGB1 in citrated and EDTA-treated plasma from the same healthy control subjects was below the limit of detection of our assay (1 ng/mL), confirming that HMGB1 in serum arises when blood is allowed to clot. This means that future studies on the role of HMGB1 in vivo should be conducted on plasma rather than serum.